Retrieval practice, with or without mind mapping, boosts fact learning in primary school children. - Stuart J Ritchie; Sergio Della Sala; Robert D McIntosh (PLoS ONE)
Retrieval practice is a method of study in which testing is incorporated into the learning process. This method is known to facilitate recall for facts in adults and in secondary-school-age children, but existing studies in younger children are somewhat limited in their practical applicability. In two studies of primary school-age children of 8-12 years, we tested retrieval practice along with another study technique, mind mapping, which is more widely-used, but less well-evidenced. Children studied novel geographical facts, with or without retrieval practice and with or without mind mapping, in a crossed-factorial between-subjects design. In Experiment 1, children in the retrieval practice condition recalled significantly more facts four days later. In Experiment 2, this benefit was replicated at one and five weeks in a different, larger sample of schoolchildren. No consistent effects of mind mapping were observed. These results underline the effectiveness of retrieval practice for fact learning in young children.